(untitled) (Biodiversitas Journal of Biological Diversity, 2014)
Pathak AK, Sarkar UK, Singh SP. 2014. Spatial gradients in freshwater fish diversity, abundance and current pattern in the Himalayan region of Upper Ganges Basin, India. Biodiversitas 15: 186-194.The present study describes the analysis and mapping of the different measurements of freshwater fish biodiversity of the Upper Ganges basin in the Himalayan region using spatial interpolation methods of Geographical Information System. The diversity, richness and abundance of fishes for each sampling location were determined and Kriging interpolation was applied on each fisheries measurement to predict and produce semivariogram. The semivariogarms produced were cross validated and reclassified. The reclassified maps for richness, abundance and diversity of fishes, occurrence of cold water threatened fish and abundance of important genera like Tor, Schizothorax and species were produced. The result of the Kriging produced good results and overall error in the estimation process was found significant. The cross validation of semovariograms also provided a better result with the observed data sets. Moreover, weighted overlay analysis of the reclassified raster maps of richness and abundance of fishes produced the classified raster map at different evaluation scale (0-10) qualitatively describing the gradient of species richness and abundance compositely. Similarly, the classified raster map at same evaluation scale qualitatively describing the gradient of species abundance and diversity compositely was produced and published. Further, basin wise analysis between Alaknanda/Pindar and Ganga1 sub basins showed 0.745 disparities at 0.745 distances in 2 dimensional spaces. The richness, diversity and abundance of threatened fishes among the different sampling locations were not significant (p = 0.9).